Functional Imaging and Modeling of the Heart
DOI: 10.1007/978-3-540-72907-5_11
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Framework to Validate 3D Models of Cardiac Electrophysiology Via Optical Imaging and MRI

Abstract: Abstract. Our aim is to develop a framework to validate 3-D computer models of cardiac electrophysiology using measurements of action potential obtained via optical imaging (based on voltage-sensitive fluorescence), and heart anatomy and fiber directions which are obtained from magnetic resonance imaging (MRI). In this paper we present preliminary results of this novel framework using a healthy porcine heart ex vivo model and the Aliev & Panfilov mathematical model. This experimental setup will facilitate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Other studies mapped the AP propagation in the presence of macroscopic obstacles created by thermally damaging the tissue using cryoablation, high intensity focused ultrasound or laser energy (Juong et al 2006, Qu et al 2004, Pastore and Rosenbaum 2000, Girouard and Rosenbaum 2001. Using our experimental set-up (Pop et al 2007) we recently reported results obtained by mapping optical AP waves in large, healthy porcine hearts. We also performed 3D model construction from MRI scans of the same hearts and adjusted the associated model based on optical measurements (Pop et al 2009a).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other studies mapped the AP propagation in the presence of macroscopic obstacles created by thermally damaging the tissue using cryoablation, high intensity focused ultrasound or laser energy (Juong et al 2006, Qu et al 2004, Pastore and Rosenbaum 2000, Girouard and Rosenbaum 2001. Using our experimental set-up (Pop et al 2007) we recently reported results obtained by mapping optical AP waves in large, healthy porcine hearts. We also performed 3D model construction from MRI scans of the same hearts and adjusted the associated model based on optical measurements (Pop et al 2009a).…”
Section: Introductionmentioning
confidence: 88%
“…The 3D optical stereo-surface of epicardium was further registered with the 3D surface of the MR image-based model as in (Pop et al 2007), via opaque markers visible in MR images, and using a rigid registration method implemented in Matlab (Horn, 1987). This step allowed us to project the measured isochronal maps onto each 3D heart mesh, similarly as presented in (Pop et al 2007 and).…”
Section: Optical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanted hearts were attached to a Langendorff perfusion system which permits to maintain the electrophysiological integrity of the hearts over 1-2 hours. The fluorescence dye (reflecting directly the changes of transmembrane potential) and the electromechanical uncoupler were injected into the perfusion line (more details are given in [9]). The hearts were paced with an electrode near the apex for 5 ms.…”
Section: Data Acquisition Processing and Fusionmentioning
confidence: 99%